79.6k views
4 votes
Solve the system of linear equations by substitution.
x + 4y = 6
x - y = 1

User Bzn
by
5.3k points

1 Answer

4 votes

9514 1404 393

Answer:

(x, y) = (2, 1)

Explanation:

Use the second equation to write an expression for x:

x = 1 +y

Substitute that into the first equation:

(1 +y) +4y = 6

5y = 5 . . . . . . . . subtract 1, collect terms

y = 1 . . . . . . . divide by 5

x = 1 +1 = 2 . . . use the expression for x to find x from y

The solution is (x, y) = (2, 1).

User Dokkaebi
by
4.1k points